Public service motivation and willingness to collaborate: An examination in the context of homeland security. Issue 1 (2014) - ,; ,
Abstract : Purpose – The purpose of this paper is to examine public service motivation (PSM) and the connection with collaborative attitudes among a sample of homeland security actors representing the public, private, and nonprofit sectors.Design/methodology/approach – This study examines relationships between measures of PSM and collaboration using original survey data and hierarchical multiple regression.Findings – Findings reveal strong positive relationships between PSM measures and attitudes toward collaboration at the individual and organizational level.Research limitations/implications – Survey results are cross‐sectional and are from respondents participating in a single state's homeland security summit.Practical implications – It is expected that results can be used to enhance collaboration at the individual and organizational levels. At the organizational level, results can be used for matching individuals with collaborative opportunities. At the individual level, results can be used for enhanced self‐reflection and effectiveness purposes.Originality/value – This study provides insights on the relationship between PSM measures and collaborative attitudes. The research contributes to the body of scholarly work connecting PSM and correlates of interest. Acknowledgements : The authors gratefully acknowledge the helpful comments received from editors and anonymous reviewers. No funding was received to support this research.